Repair of Defects of the Nasal Tip After Mohs Surgery - Sasia Pedersen; John Paoli; Robert Gniadecki; Martin Glud (Mattioli1885, 2023)
Introduction: Mohs Micrographic Surgery (MMS) is a treatment option for high-risk facial nonmelanoma skin cancer with high cure rates. Especially on the nasal tip, the tissue sparing properties of MMS are appealing. The nasal tip is a common location of nonmelanoma skin cancer and can be a challenging anatomical structure for reconstructive surgery due to its prominent location in the face, the shortage of spare tissue, as well as the stiffness and composition of different skin types, cartilage and bone. Objectives: The aim of the present paper is to review and demonstrate how reconstruction of the nasal tip can be done successfully to improve the care for patients undergoing MMS in this area. Methods: Using selected literature on the area and the surgeons experience, each method of repair are described including their individual advantages and challenges. Pictures and consent were selected from one patient who underwent each repair method and three photos are presented in this paper: one after tumor resection, one immediately after repair, and one minimum 6 months post-surgery. Results: We present eight surgical methods as well as pictures from previous surgeries. Conclusions: The results demonstrate obtainable results using very different surgical methods and the importance of an individualized approach to repairing cutaneous defects of the nasal tip.